2022
DOI: 10.14411/fp.2022.018
|View full text |Cite
|
Sign up to set email alerts
|

Different hosts in different lakes: prevalence and population genetic structure of plerocercoids of Ligula intestinalis (Cestoda) in Czech water bodies

Abstract: Ligula intestinalis (Linnaeus, 1758) is a tapeworm parasite with a worldwide distribution that uses a wide variety of fish species as its second intermediate host. In the present study, we investigated the prevalence and population genetic structure of plerocercoids of L. intestinalis in five common cyprinoid species, roach Rutilus rutilus (Linnaeus), freshwater bream Abramis brama (Linnaeus), white bream Blicca bjoerkna (Linnaeus), bleak Alburnus alburnus (Linnaeus), and rudd Scardinius erythrophthalmus (Linn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…These ecological data might be indicative of emerging host-specific races of the parasite; however, a subsequent microsatellite study using 15 polymorphic loci revealed only low genetic structuring within Lineage A, with almost no variation attributable to different fish hosts across the European continent (Štefka et al, 2009). In contrast, a recent study focusing on sympatric populations from four different fish species found nonrandom distribution of mitochondrial haplotypes between the hosts, suggesting possible evolution of host specificity (Nazarizadeh et al, 2022). Considering its unique ecological character, Lineage A presents an ideal model to explore the interactions between divergent selection pressures and ecological isolation mechanisms.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…These ecological data might be indicative of emerging host-specific races of the parasite; however, a subsequent microsatellite study using 15 polymorphic loci revealed only low genetic structuring within Lineage A, with almost no variation attributable to different fish hosts across the European continent (Štefka et al, 2009). In contrast, a recent study focusing on sympatric populations from four different fish species found nonrandom distribution of mitochondrial haplotypes between the hosts, suggesting possible evolution of host specificity (Nazarizadeh et al, 2022). Considering its unique ecological character, Lineage A presents an ideal model to explore the interactions between divergent selection pressures and ecological isolation mechanisms.…”
Section: Introductionmentioning
confidence: 80%
“…We collected 84 plerocercoid samples from five prevalent host species in Czechia: R. rutilus , A. alburnus , B. bjoerkna , S. erythrophthalmus , and A. brama (Nazarizadeh et al, 2022). These specimens were sourced from 10 different freshwater ecosystems throughout Czechia (see Table S1 and Figure 1) using gillnets, in the frame of hydrobiological research (see Nazarizadeh et al, 2022 for sampling details). The samples were fixed in 96% ethanol and subsequently stored at a refrigerated temperature prior to DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 16 plerocercoids were collected from 15 roach ( Rutilus rutilus ), caught from water bodies Želivka, Most and Klíčava in the Czech Republic according to previously described methods [23] (electronic supplementary material, table S1). To maintain uniform conditions and minimize variability in transcriptome expression, only 1-year old fish infected with a single tapeworm were selected from the Most and Klíčava water bodies (electronic supplementary material, figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…Larval worms can be induced to develop sexually in vitro [18]. The tapeworm has been extensively used in endocrinological, ecological, population genetic, phylogeographic and immunological studies [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%